Facing Crises of Unsustainability: Creating and Holding Safe Enough Spaces for Transformative Learning in Higher Education for Sustainable Development - Singer-Brodowski, Mandy; Förster, Ruth; Eschenbacher, Saskia; Biberhofer, Petra; Getzin, Sofia (Frontiers in Education, 2022)
The multiple crises of unsustainability are provoking increasing stress and unpleasant emotions among students. If higher education is to fulfill its mission to support transformation processes towards sustainable development, it must adapt its pedagogical approaches to help students deepen their critical thinking and empower them to engage in these transformation processes. For this reason, emotions – which can also prevent critical thinking – should be carefully addressed within transformative learning journeys. However, these journeys are themselves challenging for learners and educators. They push them to abandon stable meaning perspectives, causing feelings of incoherence and tension. Learners need safe enough spaces to navigate these situations of uncertainty. The central questions of this paper are: What is meant by safe enough spaces? How can learners, educators, and higher education institutions create and hold such spaces? These questions are explored on three different levels: 1) the intrapersonal level, 2) the interpersonal level, and 3) the organizational and systemic level of discourses in higher education. For the intrapersonal level, perspectives inspired by neurobiology are used to discuss reaction patterns of our autonomous nervous system and present insights into stress development. Learners should feel bodily safe when engaging in transformative learning processes. This is supported by balancing the challenges learners face with the resources they have. For the interpersonal level, the paper argues that focusing solely on rational discourse is insufficient to support safe enough spaces for transformative learning. We call for a culture of edifying conversations supported by respectful relationships among learners, as they are more adequate for regaining self-direction. For the organizational and intertwined systemic level, the ambition is followed to make higher education institutions offer learning environments that feel safe enough for all involved. However, as these institutions are strongly influenced by dynamics of economization and competition, they do not necessarily empower learners to challenge and disrupt unsustainable and neoliberal discourses. The paper explores how learners and educators can cultivate engaged critique by acknowledging their own embeddedness in neoliberal dynamics and opening up so-called transformative spaces for institutional change. Finally, recommendations for educational practices in higher education for sustainable development are offered.